Unlocking E-Banking Behavior: Unraveling the Impact of Perceived Threat and Anxiety on Coping Strategies in Kebumen District - Mahardhika, Arya Samudra (Universitas Nahdlatul Ulama Surabaya, 2023)
The goal of this study was to empirically evaluate the association between perceived threat and anxiety on coping behaviors (protective action, seeking help, avoidance) of Kebumen district e-banking users. By disseminating surveys via a Google form, 121 study samples were acquired. Purposive sampling was utilized in this study, with the criteria of respondents obtained by e-banking. In this work, structural equation modeling is used to evaluate hypotheses using the WarpPLS version 7.0 program. The findings of hypothesis testing demonstrate that perceived threats and anxiety have an influence on coping behavior; however, there is no evidence that perceived threats lead to avoidance. According to the findings of this study, threats have no effect on respondents' usage of e-banking because it has become a daily requirement.